Structural comparison of Neisseria gonorrhoeae outer membrane proteins. - Heckels, J E (1981)
Outer membranes from opaque colonia variants of Neisseria gonorrhoeae P9 contain a major outer membrane protein (protein I) together with one or more of a series of heat-modifiable proteins (proteins II). Proteins I. II, and IIa have been isolated by detergent extraction of outer membranes. Amino acid analysis showed proteins II and IIa to have a very similar composition. Cyanogen bromide cleavage of proteins II and IIa produced a pair of fragments with identical molecular weight and a pari which differed by an amount (0.5K) equivalent to the difference between the intact proteins. Tryptic peptide maps of 125I-labeled proteins II, IIa, and IIb showed many similarities, with only a few peptides unique to any one protein. Peptide maps of protein IIa from cells which had been surface labeled showed that the unique peptides were exposed on the surface. The heat-modifiable proteins thus appear to form a family of proteins with closely related structure probably differing in that part which is exposed on the bacterial surface.